HUBUNGAN KARAKERISTIK TENAGA KERJA TERHADAP KADAR ELEKTROLIT DALAM DARAH TENAGA KERJA DI LINGKUNGAN PANAS - Putri Arida Ipmawati; Maria Nadila Putri; Demes Nurmayanti; Irwan Sulistio; Winarko (Poltekkes Kemenkes Surabaya, 2023)
The performance of an industri is influenced by several factors, one of which is the productivity of its workforce. The decrease in work efficiency and productivity can be caused by the working climate, including working air temperature, working air humidity,moving air velocity, and temperatures associated with a hot workplace. In addition, inadequate conditions, such as uncomfortable weather that does not meet the criteria given, can result in a decrease in work capacity which in turn causes a decrease in work efficiency and production. The purpose of this study was to determine the relationship between labor characteristics and electrolyte levels in the blood of workers.The research method used was observational analysis which was carried out in a cross sectional manner. Sampling was carried out using a direct random approach, and the required number of samples was 31 people from a total population of 33 workers in the manufacturing department. Observation and measurement of bivariate, univariate,and descriptive data are the methods used in the data collection process.The findings show that workers have a 100% working climate above 28.2OC, withpeak temperatures reaching 30.9OC. Based on the findings, there was no relationship between workers' nutritional status and electrolyte levels in their blood (p value = 0.326; p > 0.05); however, there was a correlation between the age of the workers and their blood electrolyte levels (p value = 0.007; p 0.05); there is no relationship between years of service and electrolyte levels in the blood (p value = 0.213; p > 0.05); and there is no correlation between the electro workers